The Conceptualization of Environmental Administration Law in Environmental Pollution Control - Fatma Ulfatun Najicha; Lego Karjoko; I Gusti Ayu Ketut Rachmi Rachmi Handayani; Rosita Chandrakirana; Dian Furqani Tenrilawa (Lembaga Contrarius Indonesia, 2022)
Environment is an essential element of life. The domain offers a variety of advantages and functions for humans to carry out activities and reside there. This is normative legal research using secondary sources. According to the study's findings, environmental law enforcement can be conducted both punitively and preventatively, depending on its effectiveness and nature. The lack of coordination between sectors (government officials), the absence of a monitoring plan, and the lack of environmental supervisors are obstacles to ecological monitoring.